Zineb Sedira: Saphir - Sedira, Zineb (The Photographer's Gallery, London; Kamel Mennour and Paris Musees, France, 2006)
Exhibition catalog. Sep-Nov 2006. Contributors: Brett Rogers, Richard Dyer, Christine Van Assche, Elvan Zabunyan.
English; French
Keywords: Decolonization struggles; Revolution; TR624-835 Technology- Applied Photography; Algeria